2021
DOI: 10.1097/md.0000000000026617
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C predicts the risk of incident cerebrovascular disease in the elderly

Abstract: Background: Stroke is the third leading cause of global year of life lost in all-age and second-ranked cause of disability adjusted life years in middle-aged and elder population. Therefore, it is critical to study the relationship between vascular-related risk factors and cerebrovascular diseases. Several cross-sectional studies have shown that Cystatin C (Cys C) is an independent risk factor for cerebrovascular diseases and levels of Cys C are significantly higher in stroke patients than in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…CysC, an endogenous inhibitor of cysteine proteinase, is highly associated with cerebrovascular events. 12 , 24 , 25 There are several key findings of the present study. Firstly, serum CysC level showed a negative association with poor functional outcome in patients with HICH independent of chronic kidney function (eGFR < 60 mL/min/1.73 m2).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…CysC, an endogenous inhibitor of cysteine proteinase, is highly associated with cerebrovascular events. 12 , 24 , 25 There are several key findings of the present study. Firstly, serum CysC level showed a negative association with poor functional outcome in patients with HICH independent of chronic kidney function (eGFR < 60 mL/min/1.73 m2).…”
Section: Discussionmentioning
confidence: 50%
“…CysC, an endogenous inhibitor of cysteine proteinase, is highly associated with cerebrovascular events 12,24,25 . There are several key findings of the present study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In recent years, because creatinine (Cr) is affected by muscle quality, gender, race and diet factors, and particularly, mild and moderate declines in renal function are inaccurately displayed by GFR estimated by creatinine, cystatin C (CysC) has been considered as an alternative biomarker for GFR evaluation 6 .The secretion of CysC in serum was constant, and as a new biomarker of glomerular function, it has attracted more and more attention 7 .Previous studies have reported that even mild renal function damage may have a poor prognosis for patients with AIS 8 . Meanwhile, lots of studies have reported that the level of serum CysC increased signi cantly after stroke 9,10 . However, few scholars associate the elevated level of serum CysC with early renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%